FORMATION OF MAIN DIRECTIONS OF FOREIGN POLICY OF SPAIN IN THE LATE XX - EARLY XXI CENTURY - A. Vartumyan; M. Kardanova (Гуманитарные и юридические исследования)
Spain, after the civil war, was in international isolation for a long time. Only the restoration of democracy enabled the country to gradually take its rightful place on the world stage. In the 21st century, Spain has stepped up its foreign policy, which has acquired a stable multi-vector character, which is naturally reflected in the documents of the Spanish Foreign Ministry. The first Strategic Plan for Spain's foreign policy was presented by the Ministry of Foreign Affairs back in 2000 and marked the end of the transition period that took place in the last quarter of the twentieth century and associated with Spain's overcoming of its foreign policy isolation, and the beginning of a new stage, characterized by Spain's search for its place in the world, taking into account its resources and foreign policy ambitions. The European vector remains the leading one in Spanish foreign policy. In the XXI century, the intensity of Spain's external ties with the North American and Latin American vectors stands out. The change of power in the United States in 2021, the inauguration of President J. Biden, should have a positive effect on the dynamics of bilateral relations between Spain and the United States. The article presents the hierarchy of foreign policy diplomacy, taking into account the prioritization of its vector diplomacy. Much attention in the article is paid to the historical background and the historical and cultural factor in the formation of the main directions of Spanish foreign policy at the turn of the XX-XXI centuries, which largely determine the relationship of Madrid with the Spanish-speaking states. The author comes to the conclusion about the synthesis of the country's historical past and modern realities while building Spain's multi-vector foreign policy.